Preclinical characterization of MTX-101: a novel bispecific CD8 Treg modulator that restores CD8 Treg functions to suppress pathogenic T cells in autoimmune diseases - Gardell, Jennifer L.; Maurer, Meghan E.; Childs, Monica M.; Pham, Minh N.; Meengs, Brent; Julien, Susan H.; Tan, Cong; Boster, Daniel R.; Quach, Phoenicia; Therriault, Jon H.; Hermansky, Gleda; Patton, Daniel T.; et al. (Frontiers in Immunology, 2024)
Regulatory CD8 T cells (CD8 Treg) are responsible for the selective killing of self-reactive and pathogenic CD4 T cells. In autoimmune disease, CD8 Treg may accumulate in the peripheral blood but fail to control the expansion of pathogenic CD4 T cells that subsequently cause tissue destruction. This CD8 Treg dysfunction is due in part to the expression of inhibitory killer immunoglobulin-like receptors (KIR; specifically, KIR2DL isoforms [KIR2DL1, KIR2DL2, and KIR2DL3]); these molecules serve as autoimmune checkpoints and limit CD8 Treg activation. Here we describe the pre-clinical characterization of MTX-101, a bispecific antibody targeting inhibitory KIR and CD8, both of which are expressed on CD8 Treg. By binding to KIR, MTX-101 has demonstrated that inhibiting KIR signaling can restore CD8 Treg ability to eliminate pathogenic CD4 T cells. MTX-101 bound and activated CD8 Treg in human peripheral blood mononuclear cells (PBMC), resulting in increased CD8 Treg cytolytic capacity, activation, and prevalence. Enhancing CD8 Treg function with MTX-101 reduced pathogenic CD4 T cell expansion and inflammation, without increasing pro-inflammatory cytokines or activating immune cells that express either target alone. MTX-101 reduced antigen induced epithelial cell death in disease affected tissues, including in tissue biopsies from individuals with autoimmune disease (i.e., celiac disease, Crohn's disease). The effects of MTX-101 were specific to autoreactive CD4 T cells and did not suppress responses to viral and bacterial antigens. In a human PBMC engrafted Graft versus Host Disease (GvHD) mouse model of acute inflammation, MTX-101 bound CD8 Treg and delayed onset of disease. MTX-101 induced dose dependent binding, increased prevalence and cytolytic capacity of CD8 Treg, as well as increased CD4 T cell death. MTX-101 selectively bound CD8 Treg without unwanted immune cell activation or increase of pro-inflammatory serum cytokines and exhibited an antibody-like half-life in pharmacokinetic and exploratory tolerability studies performed using IL-15 transgenic humanized mice with engrafted human lymphocytes, including CD8 Treg at physiologic ratios. Collectively, these data support the development of MTX-101 for the treatment of autoimmune diseases.